The Implementation of the Mimicry Memorization Method in Arabic Vocabulary Learning at MI Takhassus Darul Ulum - Humaidah, Humaidah; Qomariyah, Nurul; Samoh, Tasneem (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2024)
This study aims to describe the application of the mimicry memorization method in teaching Arabic vocabulary, analyze its implementation based on its inherent characteristics, and identify the strengths and weaknesses of this method in the context of Arabic vocabulary learning among fifth-grade students at Madrasah Ibtidaiyah (MI) Takhassus Darul ʿUlum Ngaliyan, Semarang. Employing a qualitative descriptive approach through fieldwork, the research utilized data collection techniques including observation, interviews, and documentation. Data analysis followed the Miles and Huberman model, comprising data reduction, data display, and conclusion drawing. Findings reveal that the mimicry memorization method at MI Takhassus Darul ʿUlum involves processes of listening, pronouncing, imitating, and memorizing vocabulary. Its strengths include direct skill acquisition by students, accurate and proper pronunciation, ease and enthusiasm in memorizing vocabulary, improved understanding of vocabulary material, increased student engagement, and enhanced recall of vocabulary. The weaknesses identified are limited learning time during memorization, reduced student attention to the teacher’s pronunciation in noisy classroom settings, and a lack of diverse media resources.